Rate and predictors of HIV virological failure among adults on first-line antiretroviral treatment in Dar Es Salaam, Tanzania - Florence George Samizi; Onna Duuma Panga; Senga Sembuche Mulugu; Catherine Gale Gitige; Elia John Mmbaga (Journal of Infection in Developing Countries)
Introduction: Monitoring resistance to first line Antiretroviral therapy (ART) is crucial in preventing accumulation of viral mutations following the implementation of the World Health Organization “treat all” initiative. We estimated the rate and predictors of virological treatment failure among adults living with HIV/AIDS in Dar es Salaam, Tanzania.